2013
DOI: 10.1074/jbc.m113.457739
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into Aβ42 Oligomers Using Site-directed Spin Labeling

Abstract: Oligomerization of the 42-residue peptide Aβ42 plays a key role in the pathogenesis of Alzheimer disease. Despite great academic and medical interest, the structures of these oligomers have not been well characterized. Site-directed spin labeling combined with electron paramagnetic resonance spectroscopy is a powerful approach for studying structurally ill-defined systems, but its application in amyloid oligomer structure study has not been systematically explored. Here we report a comprehensive structural stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
75
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 59 publications
(67 reference statements)
14
75
0
Order By: Relevance
“…Distance measurements show two intermolecular distances at 9 -10 Å and 15-17 Å for every residue position, providing unambiguous support for the lack of parallel in-register ␤ structure in A␤42 oligomers. This work echoes a recent finding that A␤42 globulomers adopt structures distinct from fibrils (39).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Distance measurements show two intermolecular distances at 9 -10 Å and 15-17 Å for every residue position, providing unambiguous support for the lack of parallel in-register ␤ structure in A␤42 oligomers. This work echoes a recent finding that A␤42 globulomers adopt structures distinct from fibrils (39).…”
Section: Discussionsupporting
confidence: 74%
“…Expression of GroES-ubiquitin-A␤42 in E. coli and their purification were performed as previously described in Ngo and Guo (38). Expression of Usp2cc and removal of fusion protein GU to prepare full-length A␤42 was performed as previously described in Gu et al (39). The purity of A␤42 fusion proteins was checked with SDS-PAGE.…”
Section: Preparation Of A␤42 Fusion Proteins and Full-length A␤42-mentioning
confidence: 99%
“…Later, the research team of Eisenberg revealed the structure of an off-pathway, cylindrical oligomer of a segment of the amyloid-forming protein αB crystallin, that resembled a β-barrel composed of six antiparallel β-strands (72). We and other groups demonstrated that amyloidogenic proteins, such as Aβ, pass through an antiparallel β-sheet structured state, corresponding to oligomers, before undergoing a transition in structure to parallel β-sheet fibrils (58)(59)(60)(73)(74)(75). Recently, the group of Tycko demonstrated that Aβ , containing the FAD-linked Iowa D23N mutation and causing CAA, assembled into antiparallel β-sheet structured fibrils that were thermodynamically metastable and had a ribbon-like appearance (39).…”
Section: Discussionmentioning
confidence: 99%
“…Low CSF levels of Aβ , the Aβ peptide consisting of 42 amino acids, in combination with high levels of total tau and phosphorylated tau, are highly predictive biomarkers for AD (74). Other candidate biomarkers are now under study and are related to Aβ metabolism, neuronal and synaptic degeneration, inflammation, and oxidative stress (73). The relevance of an early diagnosis relies on the prospect that pharmacologic interventions will likely be more effective in generating clinical benefits if started early in AD progression, before neurodegeneration is already too advanced.…”
Section: Ad Diagnosis: a Combined Effortmentioning
confidence: 99%
See 1 more Smart Citation